2019
DOI: 10.1021/acs.analchem.9b03271
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Lipid Interactions Stabilize the Oligomeric State of BOR1p from Saccharomyces cerevisiae

Abstract: We perform an analysis of the three-dimensional cosmic matter density field traced by galaxies of the SDSS-III/BOSS galaxy sample. The systematic-free nature of this analysis is confirmed by two elements: the successful cross-correlation with the gravitational lensing observations derived from Planck 2018 data and the absence of bias at scales k 10 −3 − 10 −2 h Mpc −1 in the a posteriori power spectrum of recovered initial conditions. Our analysis builds upon our algorithm for Bayesian Origin Reconstruction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…It has been suggested that this radical structural movement is facilitated by the stabilising interactions formed between two monomers and possibly involving interactions with membrane lipids [42]. In the case of the BOR homologue from S. cerevisiae, ScBOR1p, we now have evidence that the protein can function as a monomer [43], although we can't rule out that the dimer plays a role in function. It is not clear which oligomeric states is the functional form of OsBOR3, a feature that is challenging to definitively decipher even if a high-resolution structure is available.…”
Section: Discussionmentioning
confidence: 61%
“…It has been suggested that this radical structural movement is facilitated by the stabilising interactions formed between two monomers and possibly involving interactions with membrane lipids [42]. In the case of the BOR homologue from S. cerevisiae, ScBOR1p, we now have evidence that the protein can function as a monomer [43], although we can't rule out that the dimer plays a role in function. It is not clear which oligomeric states is the functional form of OsBOR3, a feature that is challenging to definitively decipher even if a high-resolution structure is available.…”
Section: Discussionmentioning
confidence: 61%
“…The different AtBOR1 constructs were individually transformed into the FGY217 ∆ bor1p knockout S. cerevisiae strain [23]. Transformants were inoculated in 10 mL of ‐URA media supplemented with 2% w/v glucose and incubated overnight at 30 °C, 300 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…104,105 Importantly, native MS directly reveals the effects of lipid binding onto the stability and formation of protein complexes. [106][107][108] Due to several drawbacks of detergent micelles, other membrane mimetics that better resemble the lipid bilayer of biological membranes are favoured and explored. 109 However, these are usually more complex including phospholipids and scaffold proteins or polymers.…”
Section: Unravelling the Architecture Of Membrane Protein Assembliementioning
confidence: 99%
“…However, recent improvements enabled the analysis of cooperative binding of lipids, drugs or other ligands such as nucleotides or peptides 104,105 . Importantly, native MS directly reveals the effects of lipid binding onto the stability and formation of protein complexes 106–108 …”
Section: Unravelling the Architecture Of Membrane Protein Assemblies mentioning
confidence: 99%